PENGARUH NILAI HLB CAMPURAN EMULGATOR DARI PRODUK ETANOLISIS PKO DAN TWEEN 80 SERTA KONSENTRASI CMC TERHADAP PROFIL STABILITAS EMULSI MENGGUNAKAN SANTAN KELAPA - Prabowo, Hanifah Nur Indhiati; Murhadi, Murhadi; A. S., Suharyono; Subeki, Subeki (Jurnal Agroindustri Berkelanjutan, 2022)
Coconut milk is made using 1000 g of coconut and 500 mL of water that has been previously boiled. The purpose of this study was to determine the effect of the emulsifier mixture (different values of HLB) and CMC and the interaction between the two on the stability profile of coconut milk. In this study, the formulation of an emulsifier mixture from palm kernel oil (PKO) ethanollysis was used combined with Tween 80 (mixed emulsifier) with hydrophilic-lipophilic balance (HLB) values for PKO (3) and Tween 80 (15) in several compositions to produce emulsifier mixture with HLB values of 8, 9, 10, 11, 12, and 13 and CMC with concentration levels of 0%, 0.25%, 0.5%, 0.75%, 1%, 1.25%, 1, 5%, and 1.75% (w/v). The value of the best emulsifier mixture (HLB) and CMC concentration on the stability profile of coconut milk emulsion was obtained in the treatment using a mixture of emulsifier (HLB) 9 and CMC treatment with a concentration of 1.75%, which was 57.15%. The combination of emulsifier mixture treatment (HLB) with CMC, gave the best coconut milk stability value in the H5C8 combination (HLB 12+CMC 1.75%) with an average value of 100.00%.Keywords: Ethanolysis of PKO, Tween 80, HLB (Hydrophylic-Lipophilic Balance), CMC (Carboxymethyl cellulose), emulsion stability